2017
DOI: 10.5087/dad.2017.210
|View full text |Cite
|
Sign up to set email alerts
|

Signalling Implicit Relations: A PDTB - RST Comparison

Abstract: Describing implicit phenomena in discourse is known to be a problematic task, from both theoretical and empirical perspectives. The present article contributes to this topic by a novel comparative analysis of two prominent annotation approaches to discourse relations (coherence relations) that were carried out on the same texts. We compare the annotation of implicit relations in the Penn Discourse Treebank 2.0, i.e. discourse relations not signaled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…They found that their empirical results matched the theoretical mappings in more than 70% of the explicit relations, but only in less than 50% of the implicit relations. Another empirical mapping between the RST-DT and the PDTB 2.0 corpora was conducted by Polakova et al (2017). They focused only on implicit discourse relations where an exact segment span matching was possible, which included a total of 472 discourse relations.…”
Section: Previous Workmentioning
confidence: 99%
“…They found that their empirical results matched the theoretical mappings in more than 70% of the explicit relations, but only in less than 50% of the implicit relations. Another empirical mapping between the RST-DT and the PDTB 2.0 corpora was conducted by Polakova et al (2017). They focused only on implicit discourse relations where an exact segment span matching was possible, which included a total of 472 discourse relations.…”
Section: Previous Workmentioning
confidence: 99%
“…A unified framework may provide a common ground for exploring the relations of different frameworks and validating annotation consistency of a corpus. We can perform comparative corpus analysis and obtain new understanding of how information expressed in one framework is conveyed in another framework, thus validating corpus annotation consistency and finding some clues for solving problems in a framework with signals from another framework, similar to Poláková et al (2017) and Bourgonje and Zolotarenko (2019).…”
Section: Introductionmentioning
confidence: 95%
“…Lit. translation: "Neither here is_concerned a small portion..." Poláková et al, 2017), but this is yet to be investigated. We are also aware, as pointed out in Egg and Redeker (2010), that minimal, local annotations do not normally form a connected graph.…”
Section: Hierarchiesmentioning
confidence: 99%
“…Having at our disposal the Penn Discourse Treebank 3.0 annotations converted into the Prague PML format (Poláková et al, 2017), we can use the same procedure to search for hierarchical structures also in these English locally annotated data. We take into account relations of the type Explicit, AltLex and AltLexC.…”
Section: Hierarchies In the Penn Discourse Treebank 30mentioning
confidence: 99%